Navigating the Whistleblowing and Fraud Prevention Literature: A Scopus-Based Bibliometric Exploration - Ratna Marta Dhewi (Universitas Pendidikan Ganesha, 2023)
This research undertakes a thorough examination of whistleblowing and fraud prevention literature through a Scopus-based bibliometric analysis. The study identifies influential works, offering thematic insights valuable for academics and practitioners concerned with corporate accountability. The analysis of publication frequency, metrics of citation, and visualization of data covers 12,791 citations from 200 whistleblowing-related articles spanning 1982-2022. The primary keyword, strongly linked to